The tainted cup ebook - Bennett, Robert Jackson (Shadow of the Leviathan, 2024)
A Holmes and Watson–style detective duo take the stage in this fantasy with a mystery twist, from the Edgar-winning, multiple Hugo-nominated Robert Jackson Bennett “Great fantasy detective stories are too rare, but Bennett—[a] rising star of fantasy—more than delivers.”—Charlie Jane Anders, The Washington Post “A thoroughly satisfying delight from start to finish.”—Amal El-Mohtar, The New York Times Book Review NOMINATED FOR THE EDGAR AWARD • A BEST BOOK OF THE YEAR: The New York Times Book Review, NPR, Elle, BookPage In Daretana’s greatest mansion, a high imperial officer lies dead—killed, to all appearances, when a tree erupted from his body. Even here at the Empire’s borders, where contagions abound and the blood of the leviathans works strange magical changes, it’s a death both terrifying and impossible. Assigned to investigate is Ana Dolabra, a detective whose reputation for brilliance is matched only by her eccentricities. Rumor has it that she wears a blindfold at all times, and that she can solve impossible cases without even stepping outside the walls of her home. At her side is her new assistant, Dinios Kol, magically altered in ways that make him the perfect aide to Ana’s brilliance. Din is at turns scandalized, perplexed, and utterly infuriated by his new superior—but as the case unfolds and he watches Ana’s mind leap from one startling deduction to the next, he must admit that she is, indeed, the Empire’s greatest detective. As the two close in on a mastermind and uncover a scheme that threatens the Empire itself, Din realizes he’s barely begun to assemble the puzzle that is Ana Dolabra—and wonders how long he’ll be able to keep his own secrets safe from her piercing intellect. By an “endlessly inventive” ( Vulture ) author with a “wicked sense of humor” (NPR), The Tainted Cup mixes the charms of detective fiction with brilliant world-building to deliver a fiendishly clever mystery that’s at once instantly recognizable and thrillingly new.